An investigation of the determinants of estate and retirement planning in intergenerational family businesses - S. P. Van Der Merwe (South African Journal of Business Management, 2009)
This study highlighted the importance of estate and retirement planning in small and medium-sized family businesses. Data from 504 questionnaires linked to 81 family businesses were collected and analysed. An Oblimin oblique rotation was performed on the principal components of the exploratory factor analysis. Five factors with eigenvalues greater than one, explaining 65.78% of the variance, were extracted. These five factors describing the theoretical dimensions of retirement planning, perceived fairness of the will, estate taxes, perceived liquidity of the business after succession and acquiring equity ownership were extracted. No practical significant differences could be found between the perceptions of male and female respondents as well as between family members involved in medium-sized or small businesses with regard to the five factors. Practical recommendations are suggested to ensure a smooth final transfer of the management and control of the business to the next generation family members.
Keywords: 650